The Times of the End (Anclajes, 2022)
The present work aims to rethink, putting the axis in temporality, the problems posed by the imagination of the end (of the current existing world). To do this, we propose an itinerary across the interventions around the pandemic expansion of COVID-19, which have put into play the logic of a radical end to address the singularity of this phenomenon. It seeks to analyze how the temporalities played out in these essays allows us to go in depth in the previous reflections on these imaginaries (particularly in their apocalyptic form). Secondly, the critical tools arising from this exploration are used to return to the ways of configuring the after the end in the trilogies published by Oliverio Coelho, Rafael Pinedo and Carlos Ríos between 2003 and 2015, emphasizing how they are constituted as long-term narrative projects that, through the way they articulate their episodes, enable a unique staging of the temporal thickness that is elaborated in the formulation of their endings. This highlights the way in which the hybridization operates on the pairs chronology / heterochrony, continuity / anachronism, successivity / simultaneity.
Keywords: Argentine Literatura; Literary Criticism; Literary Theory; XXI Century; Argentina